Italy must foster high growth industries - Stefan Gebauer; Alexander S. Kritikos; Alexander Kriwoluzky; Anselm Mattes; Malte Rieth (DIW Weekly Report, 2019)
Italy has yet to recover from the economic consequences of the financial and sovereign debt crisis that began more than a decade ago. In addition to losing 1.4 million jobs across the manufacturing and construction sectors, new industries driving growth across the EU, such as knowledge-intensive services, are instead stagnating in Italy. Previous structural reforms focused on deregulating the labor markets and on restructuring the state budget. Other framework conditions, such as an efficient innovation system or substantial R&D investments, were ignored. Going forward, governmental reforms should focus on creating such growth-friendly conditions for businesses in future-oriented industries. Our own calculations show that increased government spending within the amount provided in the latest draft budget can, in principle, have a positive short-term effect on value added, thus mitigating the adjustment costs of pending reforms. Unfortunately, the current government's plans barely fulfill these criteria.
Keywords: L2; O3; O4; 330; Italy; economic structure; growth sectors; innovation; manufacturing; SME; regulatory environment; knowledge-intensive services